1998
DOI: 10.1111/j.1540-8167.1998.tb01837.x
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Pharmacologic and Ablative Therapy: A Novel and Effective Approach for the Management of Atrial Fibrillation

Abstract: In patients who experience conversion of atrial fibrillation to atrial flutter during antiarrhythmic drug treatment, ablation and continuation of pharmacologic therapy is a safe and effective means of achieving and maintaining sinus rhythm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
63
0
6

Year Published

1998
1998
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 138 publications
(73 citation statements)
references
References 20 publications
3
63
0
6
Order By: Relevance
“…25,26 In patients with episodes of both AFl and AF, flutter ablation may have different effects on the incidence of AF. [27][28][29] Nabar et al 30 noted a marked reduction in AF episodes after flutter ablation in patients with AFl as their dominant arrhythmia.…”
Section: Wellens Contemporary Management Of Atrial Fluttermentioning
confidence: 99%
“…25,26 In patients with episodes of both AFl and AF, flutter ablation may have different effects on the incidence of AF. [27][28][29] Nabar et al 30 noted a marked reduction in AF episodes after flutter ablation in patients with AFl as their dominant arrhythmia.…”
Section: Wellens Contemporary Management Of Atrial Fluttermentioning
confidence: 99%
“…[165][166][167] Prospective trials have shown that, if atrial flutter becomes the dominant rhythm, then ablation of the CTI and continued use of the antiarrhythmic drug result in a decreased incidence of atrial flutter and facilitate the pharmacologic management of AF. 168,169 The incidence of AF after successful ablation of the CTI flutter circuit varies, depending on the presence of AF before ablation. For patients with a history of only atrial flutter, the occurrence of AF over a follow-up of 18 plus or minus 14 months was only 8%.…”
Section: H Catheter Ablation Of the Cavotricuspid Isthmus For Isthmumentioning
confidence: 99%
“…[1][2][3][4][5][6][7] But, in the clinical setting, AFL and atrial fibrillation (AF) often coexist, and the follow up of patients successfully treated with transisthmic ablation is complicated by the occurrence of AF in 10~47% of patients. [8][9][10][11][12][13][14][15][16][17] We already have known that the presence of preablation AF is the most significant predictor of postablation AF. [18][19][20] However, clinical and procedural predictors of postablation AF occurrence has always been evaluated in the mixed group of AFL patients with AF [18][19][20] and rarely in the group of patients without history of AF.…”
Section: Introductionmentioning
confidence: 99%